1987
DOI: 10.1007/bf02646201
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of aluminum-lithium alloys at cryogenic temperatures

Abstract: The cryogenic mechanical properties of aluminum-lithium alloys are of interest because these alloys are attractive candidate materials for cryogenic tankage. Previous work indicates that the strength-toughness relationship for alloy 2090-T81 (Al-2.7Cu-2.2Li-0.12Zr by weight) improves significantly as temperature decreases. The subject of this investigation is the mechanism of this improvement. Deformation behavior was studied since the fracture mode did not change with temperature. Tensile failures in 2090-T81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(24 citation statements)
references
References 19 publications
1
22
1
Order By: Relevance
“…These values are larger (about 50 percent) than those reported by Glazer, et al [9] from data on an earlier vintage 2090-T81 at equivalent test temperatures and orientation (L) . Our strain rate (9xl0~-^s"^) was about an order of magnitude lower than that used by Glazer, et al However, except at 4 K, this effect on strainhardening rates is expected to be insignificant.…”
Section: Ductilitycontrasting
confidence: 52%
See 2 more Smart Citations
“…These values are larger (about 50 percent) than those reported by Glazer, et al [9] from data on an earlier vintage 2090-T81 at equivalent test temperatures and orientation (L) . Our strain rate (9xl0~-^s"^) was about an order of magnitude lower than that used by Glazer, et al However, except at 4 K, this effect on strainhardening rates is expected to be insignificant.…”
Section: Ductilitycontrasting
confidence: 52%
“…The increase of E at low temperatures is approximately 10 percent, of the same order as the increase in E for pure Al [6]. ASTM E 1304 S-L 10,9 (9,8) S-T 10,10 (9.9) Ledbetter, 1990, dynamic data (x)®; MIL-HDBK recommended value for 2219 (n)^.…”
Section: 21mentioning
confidence: 94%
See 1 more Smart Citation
“…Mechanical properties are mainly dependent on the composition, phase structure and defects, but not constant and often changes as a function of temperature. Materials often have some undesirable or unusual properties in cryogenic temperatures that make them interesting or unsafe to use in cryogenic engineering [2,[4][5][6][7]. For example, the body-centred-cubic metals show good fracture toughness at room temperature but brittleness at cryogenic temperatures [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed an excellent strength-toughness combination for 2090 at cryogenic temperatures.£6, [8][9][10][11][12][13] Subsequently, much of the work on 2090 has concentrated on understanding the source of the excellent mechanical properties observed at cryogenic temperatures.£1- 3,6,[8][9][10][11][12][13][14] Although the determining mechanism remains an issue of debate, it is generally agreed upon that the deformation behavior, the ability of a material to work harden, plays an important part in determining the subsequent fracture toughness.£6, 8,1O,12] The majority of work on 2090 and other like alloys associates increases in workhardening with greater slip homogeneityJI5-17] Jata and Starke [16] relate this greater homogeneity with a decrease in slip planarity. The planarity of slip is, in turn, controlled by the ability of dislocations to cross-slip.…”
Section: Introductionmentioning
confidence: 99%